Combined effect of prefermentative cold soak and SO2 additions in Barbera D’Asti and Malbec wines : anthocyanin composition, chromatic and sensory properties - Casassa, Luis Federico (2016)
The effects of prefermentative cold soak (CS) combined with two SO2 additions (50 and 100 mg L1) on the anthocyanin composition, chromatic properties and sensory attributes of Barbera D'Asti and Malbec wines were studied. Cold soak had no effect on the basic chemistry of the wines. The cultivar factor affected anthocyanins, tannins, total phenolics and the chromatic features of the wines, favoring Malbec over Barbera D'Asti wines. Cold soak combined with 50 mg L1 SO2 failed to increase the phenolic content of the wines relative to a control, but combined with 100 mg L1 SO2, CS increased anthocyanins, saturation and the red color component of the wines. Cold soak þ 100 mg L1 also increased the sensory attributes color intensity, violet hue, jammy aroma and astringency in Barbera D'Asti wines but there was no effect of any treatment on the sensory properties of Malbec wines. Overall, CS combined with an SO2 addition of 100 mg L1 appears to have a positive effect but only from the perspective of wine phenolics and color.